Analisis Perbandingan Pengaturan Ibu Kota dalam Konstitusi Global: Pelajaran bagi Ibu Kota Baru Indonesia - Jaya, Akbar Arta (Jurnal Konstitusi & Demokrasi, 2024)
On August 16, 2019, the President of the Republic of Indonesia, Joko Widodo, delivered a state speech ahead of Indonesia's Independence Day commemoration, in which the plan to move the national capital to Kalimantan was presented. The relocation of the capital city in a country has various motives, including the location of the previous capital city which is vulnerable to threats from other countries, the development of new cities, and increasing economic growth. This research was conducted to see how the constitutions of countries in the world, especially in 25 countries in the Asian continent (11 Southeast Asian countries, 7 South Asian countries, and 6 East Asian countries) as well as 12 Latin American countries, 7 Central America, 5 European countries (England, France, the Netherlands, Spain, and Portugal), and 2 superpowers namely the United States and Russia, regulate the capital city. The research method used is normative juridical, with a comparative approach. Through this approach, the author conducts research by comparing 2 (two) or more countries' constitutions in regulating the capital city. From the results of the research, the author found that there are 33 countries that regulate the capital city in their constitutions. This number is quite a lot, which is 66% when compared to 17 countries or 34% that do not regulate the National Capital. In the final section, the author recommends that Indonesia can follow model 1 and model 2 in a limited way, considering that currently Indonesia has been trying to successfully move the National Capital to Kalimantan.